Predictors of survival among end stage renal failure patients undergoing dialysis treatment in Pahang from 2000 TO 2004 - AJ Hamid,; MT Azmi, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Introduction : A retrospective cohort study was conducted among ESRD who received dialysis treatment (Haemodialysis and CAPD) in all government hospitals in the State of Pahang from 1st January 2000 to 31st December 2004. Objective : The aim of the study was to identify factors affecting the survival of patients undergoing dialysis in the state of Pahang. Methods : Survival time was measured from the date of dialysis until the subjects died, lost to follow up or until the end of the study period at 31st December 2004. Results : Diabetes mellitus was the major cause for ESRD (33%) out of 132 subjects eligible for the study. Seven (7.1%) and five (15.2%) deaths occurred among haemodialysis and CAPD patients respectively, but statistically of no difference between the two treatments (log-rank, p=0.093). Factors influencing the survival of haemodialysis patients were diabetes mellitus (p=0.014), albumin (p=0.0005), creatinine (p=0.020) and hemoglobin level (p=0.002), while age of treatment and diabetes mellitus affecting the survival of CAPD patient. Cox Proportional Hazard Regression showed that haemodialysis subjects with low albumin (HR 0.669 df 95% 0.513 - 0.873) and hemoglobin (HR 0.403 df 95% 0.225 - 0.720) level had lower survival rate but none for CAPD. Conclusion : Good nutritional status, higher hemoglobin level and prevention of diabetes mellitus are important for the survival of haemodialysis patient.